ANALYSIS OF THE FACTORS THAT INFLUENCE HYPERTENSION INCIDENCE IN PENITENTIARY X KALIMANTAN - Fendy Yesayas; Fatima Ura Pabanne; Donny Richard Mataputun (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
Hypertension is a non-communicable disease which is one of the main causes of premature death in the world. The purpose of this study The purpose of this study was to determine the relationship between lifestyle and the incidence of hypertension in Correctional Institutions (Lapas) Class IIA Tarakan City. Research design This research is a quantitative research. The type of research used in this research is descriptive analytic with a cross sectional approach. In this study, the dependent variable was the incidence of hypertension. The independent variables are physical activity, sleep patterns, family history of HT and history of hypertension. The confounding variables are Age, Gender, Last Education. The sampling technique used in this study was purposive sampling with a total sample of 50 samples. Collecting data using a questionnaire and the results of blood pressure measurements, then analyzed bivariate with the Kendall tau test and multivariate using logistic regression test. The results showed that there is no relationship between age and the incidence of hypertension (pvalue 0, 327), there is a significant relationship between family history and the incidence of hypertension (Pvalue 0.020), there is a significant relationship between history of hypertension and the incidence of hypertension (Pvalue 0.012, there was a relationship between physical activity and the incidence of hypertension (Pvalue 0.028), there was a significant relationship between sleep patterns and the incidence of hypertension (PValue 0.000), sufferers, history of hypertension, physical activity and sleep patterns on The incidence of hypertension (Pvalue <0.05). This research is expected to be a source of developing nursing knowledge related to independent nursing interventions.